Creatine (Cr) supplementation and swimming - Jacobs, K. A.; Leenders, N. Y.; Sherman, W. M.; Nelson, T. E.; Lamb, D. R.; Miller, E. C. (Medicine & Science in Sports & Exercise, 1998)
Two weeks of creatine ingestion was evaluated as to whether it would or would not improve swimming velocity over 50-m (6 x 50 m twice a week) and 25-yd (10 x 25 yd twice a week) intervals. College swimmers (M = 18; F = 14) served in a double-blind study after a two-week period of placebo (baseline) supplementation. There was no effect of creatine supplementation on the 10 x 25-yd intervals for either gender. There was no effect of creatine supplementation on the 6 x 50-m set in females but there was in males. These data suggest that short swimming intervals (10-15 sec) are not affected by creatine and males, but not females, do improve marginally over repetitious intervals of 30-35 seconds.Implication. Female swimming performance is not benefited by creatine supplementation but males do improve over 30-35 second repetitious tasks.